Effect of Bioptron Light Therapy on post-menopausal low back pain: A randomized controlled study - Elemam Ahmed, Mohamed Abdelbaset; Mohamed Awad, Mohamed Ahmed; Abdel Aziz Atta Allah, Abdel Hamid; Mustafa Saleh, Marwa Shafiek; Rashad Aboelmagd, Shreen (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
Women's bodies undergo numerous changes throughout the post-menopausal period, many of which result in uncomfortable symptoms, including skeletal problems such as low back pain (LBP). The aim of this study was to evaluate the impact of Bioptron Light Therapy (BLT) on post-menopausal LBP in women. This study employed a pretest-posttest randomized experimental trial design. Forty post-menopausal women with LBP, aged 50 to 60 years, were randomized into two groups (study and control group). The control group (Group A, n=20) received abdominal and back isometric exercises only, whereas the study group (Group B, n=20) received BLT in addition to the same isometric exercises, three sessions per week for six weeks. Pain severity using the Visual Analogue Scale (VAS), Pain Pressure Threshold (PPT) using a pressure algometer, and functional disability using the Modified Oswestry Disability Questionnaire (MODQ) were measured for all patients in both groups before and after the treatment program. The Statistical Package of Social Sciences (SPSS) (version 19) was used for data analysis. Based on the results of our study, PPT significantly increased in both groups after treatment (p = 0.0001), with the study group showing a greater increase than the control group (p = 0.001). Pain intensity decreased significantly in both groups (p = 0.0001), with a statistically significant difference favoring the study group (p = 0.0001). MODQ scores also significantly decreased in both groups (p = 0.0001), again favoring the study group (p = 0.0001). BLT can be included as a valuable, effective, and non-invasive method for decreasing pain and improving function for women with post-menopausal LBP.